Procedural times with robotic-assisted bronchoscopy: a high volume single-center study - Kim Styrvoky; Audra Schwalk; David Pham; Kristine Madsen; Hsienchang Chiu; Muhanned Abu-Hijleh (Therapeutic Advances in Respiratory Disease, 2024)
Background: Incidental and screen-detected pulmonary nodules are common. The increasing capabilities of advanced diagnostic bronchoscopy will increase bronchoscopists’ procedural volume necessitating optimization of procedural scheduling and workflow. Objectives: The objectives of this study were to determine total time in the procedure room, total bronchoscopy procedure time, and robotic-assisted bronchoscopy procedure time longitudinally and per specific procedure performed. Design: A single-center observational study of all consecutive patients undergoing shape-sensing robotic-assisted bronchoscopy (RAB) biopsy procedures for the evaluation of pulmonary lesions with variable probability for malignancy. Methods: Chart review to collect patient demographics, lesion characteristics, and procedural specifics. Descriptive and comparative statistics are reported. Results: Actual bronchoscopy procedure time may decrease with increased institutional experience over time, however, there is limited ability to reduce non-bronchoscopy related time within the procedure room. The use of cone beam computed tomography (CBCT), rapid on-site evaluation (ROSE), and performance of staging endobronchial ultrasound transbronchial needle aspiration (EBUS-TBNA) in a single procedure are each associated with additional time requirements. Conclusion: Institutional procedural block times should adapt to the nature of advanced diagnostic bronchoscopy procedures to allow for the accommodation of new modalities such as RAB combined with other technologies including radial endobronchial ultrasound, CBCT, ROSE, and staging linear EBUS. Identifying institutional median procedural times may assist in scheduling and ideal block time utilization.